ANALISIS EFEKTIVITAS DAN KONTRIBUSI PENERIMAAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN TERHADAP PENDAPATAN ASLI DAERAH PADA KABUPATEN SAMOSIR - Situmorang, Roita; Silalahi, Evelin Roma Riauli (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This research aims to determine the level of effectiveness and how big the contribution of land and building rights acquisition fees is to local original income in Samosir Regency. The population in this study is target data and realization of Land and Building Rights Acquisition Fees and Original Regional Income since it was implemented in 2011-2022 at the Samosir Regency Regional Revenue Agency. The sample in this study is the realization and target of receipt of Land and Building Rights Acquisition Fees and Original Regional Income from 2018-2022 at the Samosir Regency Regional Revenue Agency. The data collection technique in this research was carried out using documentation techniques. The data analysis technique used in this research is a descriptive analysis technique with a formula for level of effectiveness and level of contribution.The results of the research conducted show that the overall effectiveness level of acceptance of Land and Building Rights Acquisition Fees from 2018-2022 is categorized as